Analysis of reports on orphan lung diseases in Korean children - Sun Jung Jang; Hyun Kyung Seo; Sung Jae Yi; Kyong Min Kim; Hye Mi Jee; Man Yong Han (Korean Pediatric Society, 2010)
PurposeOrphan lung diseases are defined as lung diseases with a prevalence of 1 or less in 2,000 individuals. Despite an increase in the numbers of patients with such diseases, few studies on Korean children have appeared. To obtain epidemiologic and demographic data on these diseases, we systematically reviewed reports on pediatric orphan lung diseases in Korea over the last 50 years.MethodsWe reviewed 223 articles that have appeared since 1958 on orphan lung diseases in Korean children. These articles described a total of 519 patients aged between 0 and 18 years. We classified patients by year of publication, diagnosis, geographic region, and journal.ResultsOf 519 patients, 401 had congenital cystic lung diseases and 66 had bronchiolitis obliterans. About 80% of patients were described in reports published in three journals, Pediatric Allergy and Respiratory Disease (Korea), the Korean Journal of Pediatrics, and the Korean Journal of Thoracic and Cardiovascular Surgery, in which papers on 157 (30.2%), 138 (26.6%), and 111 (21.4%) patients appeared, respectively. The frequency of publication of case reports has increased since 1990. Of the 519 patients, 401 (77.3%) were from Seoul/Gyeonggi-do and 72 (13.9%) from Busan/Gyeongsangnam-do.ConclusionThe prevalence of pediatric orphan lung disease has increased since 1990, and some provinces of Korea have a higher incidence of these diseases than do others. Studies exploring the incidence of pediatric orphan lung diseases in Korea are needed for effective disease management.